FAMILIARITY MAHASISWA POLITEKNIK NEGERI PADANG TERHADAP VIRTUAL EVENT SEBAGAI ALTERNATIF DALAM MENGHADIRI EVENT PADA SAAT PANDEMI COVID-19 - Rafidola Mareta Riesa; Alfatah Haries; Sepri Neswardi (Akademi Pariwisata Bunda Padang, Sumatera Barat, Indonesia, 2021)
The pandemic has shifted the pattern of organizing events and has to adapt to new habits, namely holding the events in a virtual way. This shift has an impact on students who often take part in offline events to online or virtual. This study aims to see the extent to which Politeknik Negeri Padang students are familiar with virtual events. Data collection techniques were carried out through a questionnaire by looking at four indicators, namely informational, experiential, self-rated, and educational. The results showed that the majority of Politeknik Negeri Padang students receive information about virtual tour through social media. The majority of students have participated in virtual events and think they are quite familiar with virtual events. The study also found that most students gained knowledge about virtual events when they took formal education.